Peningkatan dan Aktivitas Hasil Belajar Peserta Didik Menggunakan Model Pembelajaran Kooperatif Tipe TAI (Team Assisted Individualization) pada Mata Pelajaran Kewirausahaan Kelas XI SMK Negeri 1 Sakra - Hermany Hermany (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2019)
This study aims to determine (1) increased activity, and (2) student entrepreneurship learning outcomes through the implementation of the cooperative learning model type TAI (Team Assisted Individualization) in class XI Multimedia students of SMK Negeri 1 Sakra. This research is a classroom action research conducted in two cycles with the stages of each cycle including planning, action, observation and evaluation, and reflection. Learning activity data collected by the method of observation and learning outcome data collected through the test method. Data collected was analyzed using quantitative descriptive analysis. The results showed that, (1) the implementation of the TAI type of cooperative learning model can increase the learning activities of students as indicated by the average score of learning activities in the first cycle of 33.5 with the category of active enough and then increased to 39.25 with the active category in the cycle II. (2) Implementation of the TAI type of cooperative learning model can improve student learning outcomes as indicated by an average score of learning outcomes in the first cycle of 77.12 with sufficient categories subsequently increased to 89.35 with very good categories in the second cycle.